COVID-19 and EU climate targets: Going further with less? - Tensay Hadush Meles; Lisa Ryan; Joe Wheatley (University College Dublin, UCD Centre for Economic Research, 2020)
The COVID-19 crisis comes at a complex moment for European climate policy as it pivots from a 40% 2030 emissions reduction target to a European Green Deal that is in better alignment with long-term Paris Agreement goals. Here, the implications of the dramatic fall in economic output associated with the crisis are examined using a representative range of growth scenarios. With lower economic activity resulting from the COVID-19 crisis, existing policy measures could achieve the 40% target sooner than 2030. However, we find that even in the most severe economic scenario examined, this falls well short of the 50-55% emissions reduction target under the Green Deal. Maintaining the existing 40% target in 2030 with reduced policy measures on the other hand would move European climate policy away from the required path. This analysis indicates the feasibility of increased climate ambition in the wake of the pandemic and supports the Green Deal 50-55% targets in 2030.
Keywords: Q50; Q54; Q58; E60; Q43; 330; climate change policy; greenhouse gas emissions; economic recovery; COVID19 economic effects; energy demand